Economic incentives to renovation in tourism accommodation: The market of building rights - Santos Chinea, María Candelaria; Simancas Cruz, Moisés; Hernández Martín, Raúl (Cuadernos de Estudios Empresariales, 2015)
Current tourism policy in Canary Islands revolves around the renovation of both, areas and tourist accommodations that could be classified as obsolete. The legislation provides a package of incentives aimed at making attractive renovation operations that go beyond mere rehabilitation of hotels. It also includes mechanisms to promote and to make economically viable replacement processes of these establishments. One of these mechanisms is related to obtaining building rights that can be used to build new tourism accommodation places as an incentive for the implementation of an accommodation renovation project. Theses building rights are not affected by the quantitative restrictions to the development of new hotels that are applied in the Canary Islands. In this paper we analyze the weaknesses and opportunities arising from the market of building rights in tourism accommodation.
Keywords: mature destinations; tourist accommodation; economic incentives; Canary Islands; tourism policy; renovation